Comparison of Wire Trap (Temilar) Catch Yields between Daytime and Nighttime Operations in Tarikan Village, Muaro Jambi Regency - Aditya Eka Apriliyanto; Pramusintho, Bagus; Lisna, Lisna (Fakultas Perikanan dan Kelautan Universitas Riau, 2025)
The purpose of this study was to determine the differences in catch results of wire traps (temilar) between daytime and nighttime operations. The research was conducted in the waters of the Kumpeh River, Tarikan Village, Muaro Jambi Regency. The method used in this study was experimental fishing and simple random sampling with 15 replications, using two treatments: daytime and nighttime operations. Based on the results of the survey, nine species of fish were caught. The dominant species was the lambak (Labiobarbus ocellatus), with a total of 212 individuals and an overall catch of 814 individuals obtained during nighttime trap operations. The heaviest catch was the tembakang (Helostoma temminckii), with an individual weight of 7,266 grams and a total weight of 28,871 g, also obtained from the use of wire traps (temilar) at night. The t-test results showed a significant difference (P < 0.05) in both the number and weight of catches between daytime and nighttime wire trap (temilar) operations. Based on these findings, it can be concluded that nighttime operation of wire traps (temilar) yields higher catches, both in number and total weight, compared to daytime operations